Apical constriction: themes and variations on a cellular mechanism driving morphogenesis - Martin, Adam C; Goldstein, Bob (Development (Cambridge), 2014)
Apical constriction is a cell shape change that promotes tissue remodeling in a variety of homeostatic and developmental contexts, including gastrulation in many organisms and neural tube formation in vertebrates. In recent years, progress has been made towards understanding how the distinct cell biological processes that together drive apical constriction are coordinated. These processes include the contraction of actin-myosin networks, which generates force, and the attachment of actin networks to cell-cell junctions, which allows forces to be transmitted between cells. Different cell types regulate contractility and adhesion in unique ways, resulting in apical constriction with varying dynamics and subcellular organizations, as well as a variety of resulting tissue shape changes. Understanding both the common themes and the variations in apical constriction mechanisms promises to provide insight into the mechanics that underlie tissue morphogenesis.